PENGEMBANGAN MEDIA PERMAINAN KARTU KUARTET UNTUK MENINGKATKAN PEMAHAMAN TENTANG BULLYING PADA SISWA SEKOLAH DASAR - Nurmalasari; Siti Muhibah; Alfiandy Warih Handoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the problem of rampant acts of bullying in elementary schools, which can have a negative impact on students' social and emotional development. One preventive measure that can be taken is to educate students about bullying. This study aims to develop a quartet card game to improve elementary school students' understanding of bullying. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analyze, design, development, implementation, and evaluation. The research subjects are upper grade students (grades IV-VI) at SDN Cilaja 3. The data collection techniques used included interviews and questionnaires.The results of the study show that media and material expert validation scored 95% (highly feasible), language expert validation scored 89% (highly feasible), and practitioner expert validation scored 100% (highly feasible). Thus, the average score of all assessments was 95%, which is highly feasible for use and implementation. In addition, a limited trial of the media was conducted on 6 upper grade students (representatives of grades V-VI) and produced an average score of 90% with a very feasible category. Furthermore, the pre-test and post-test results showed an increase in understanding of bullying from the low category to the high category, with an average N-Gain score of 81%, which is included in the effective category. Based on these results, the quartet card game media is considered highly feasible and can be used as an alternative media to improve students' understanding of bullying in elementary schools.